PENANAMAN NILAI KARAKATER GOTONG ROYONG MELALUI PERMAINAN TRADISONAL BAKIAK PADA PESERTA DIDIK KELAS IV DI SD INPRES LAMBENGI - Sam'un Mukramin; Sri Rahayu Nengsi; Linda Pajarwati; Widia Dwi Lestari; Sulfa R; Ulfa Dwianti; Sukriadi Sukriadi (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Traditional games have long been a means of children's play and have been passed down from generation to generation. Traditional games are beneficial for children's physical and mental development. This traditional game is classified as a means of entertainment, a means of competition, and a means of education. Traditional games have many forms, including clog games which of course have educational value that can be utilized by children. Bakiak itself has a deep philosophical meaning, which means it reflects the social and cultural values that exist in society, especially in the Gowa Regency area, within the Inpres Lambengi Elementary School environment. There are several philosophical meanings that can be taken from playing clogs. Based on the results of the analysis, it was found that by using traditional games, material processes, relational processes and behavioral processes can be found when making the Bakiak game as a game for learning media. Among these three processes, the material process is very dominant. This shows that clogs tend to be described as a physical sport carried out in groups and a good learning medium for students at SD Inpres Lambengi in instilling character values